Saving Endangered Species : Lessons in Wildlife Conservation from Indianapolis Prize Winners - Shumaker, Robert W. (Book collections on Project MUSE., 2020)
"This edited volume has contributions by wildlife biologists and conservation champions, all winners of the prestigious Indianapolis Prize. In telling their stories of working to conserve animal species, the contributors explain key concepts in wildlife conservation science and suggest pathways for how to pursue a career in the field. The book is geared toward course use and emerging professionals"--